Novel Design for Quantum Dots Cellular Automata to Obtain Fault-Tolerant Majority Gate - Razieh Farazkish; Samira Sayedsalehi; Keivan Navi (Journal of Nanotechnology)
Quantum-dot Cellular Automata (QCA) is one of the most attractive technologies for computing at nanoscale. The principle element in QCA is majority gate. In this paper, fault-tolerance properties of the majority gate is analyzed. This component is suitable for designing fault-tolerant QCA circuits. We analyze fault-tolerance properties of three-input majority gate in terms of misalignment, missing, and dislocation cells. In order to verify the functionality of the proposed component some physical proofs using kink energy (the difference in electrostatic energy between the two polarization states) and computer simulations using QCA Designer tool are provided. Our results clearly demonstrate that the redundant version of the majority gate is more robust than the standard style for this gate.